2021
DOI: 10.51948/auad.910385
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal bilgiler öğretmen adaylarının covid-19 salgını sürecinde uzaktan eğitim deneyimleri ve görüşleri

Abstract: Koronavirüs (COVID-19) salgını sebebiyle Türkiye dahil birçok ülkede, 2019-2020 eğitim-öğretim yılının bahar döneminde, örgün eğitimden uzaktan eğitime geçilmiştir. Bu dönemde sosyal mesafeyi koruma önlemleri kapsamında sokağa çıkma yasakları uygulanmıştır. Acil olarak başlatılan uzaktan eğitim, öğretim yöntem ve uygulamalarının değişmesine sebep olmuştur. Salgın sürecinin uzun sürmesi, öğrenmeye ayrılan zamanı ve öğrencilerin öğrenme fırsatlarını sınırlandırmıştır. Araştırmanın amacı sosyal bilgiler öğretmen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0
30

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 8 publications
7
22
0
30
Order By: Relevance
“…First of all, the results of these advantages indicate that it allows using of different materials and tools, maintaining education, and learning technology, and eliminating the necessity of time and place. These results are similar to the findings of studies conducted by Akgül and Oran (2020), Korkut and Memişoğlu (2021), Seyhan (2021), and Uyar (2020). Participants in the related studies emphasized distance education functions, such as sharing materials, maintaining education appropriately, and eliminating the necessity of time and place.…”
Section: Discussionsupporting
confidence: 92%
“…First of all, the results of these advantages indicate that it allows using of different materials and tools, maintaining education, and learning technology, and eliminating the necessity of time and place. These results are similar to the findings of studies conducted by Akgül and Oran (2020), Korkut and Memişoğlu (2021), Seyhan (2021), and Uyar (2020). Participants in the related studies emphasized distance education functions, such as sharing materials, maintaining education appropriately, and eliminating the necessity of time and place.…”
Section: Discussionsupporting
confidence: 92%
“…In Sirem & Baş's (2020) study, the most difficult case for students in the distance education process due to the COVID-19 epidemic was to have difficulty in understanding and not reviewing the subjects. In the research conducted by Seyhan (2021), it was determined that pre-service teachers had difficulties in getting materials, accessing the Internet, providing a learning environment, and that students had learning difficulties in distance education. In the study conducted by Aktan Acar,…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, they need to develop their technical infrastructure. Almaghaslah and Alsayari [2], Alpaslan [3] and Kurnaz and Sercemeli [18] have examined the views of academicians on distance education. In the results obtained, it was concluded that in-service training should be given in order to change the perspectives of academicians towards distance education.…”
Section: Conclusion Recommendations and Discussionmentioning
confidence: 99%
“…These trainings are 'management and leadership', 'managerial development programme', 'stress management', 'effective presentation technique' and 'time method'. When the order of importance of the training given to the administrators was requested, it was found that the most effective trainings were 'management and leadership' (12), 'stress management' (3) and 'time management' (3). Trainings given during the process can be increased.…”
Section: Conclusion Recommendations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation